Eating out of home: energy, macro- and micronutrient intakes in 10 European countries. The European Prospective Investigation into Cancer and Nutrition. - Orfanos, P; Naska, A; Trichopoulou, A; Grioni, S; Boer, J; Bakel, v; Ericson, U; Rohrmann, S; Boeing, H; Rodríguez, L; Ardanaz, E; Sacerdote, C; et al. (2009)
OBJECTIVES: To assess the contribution of out-of-home (OH) energy and nutrient intake to total dietary intake, and to compare out- versus in-home nutrient patterns among 27 centres in 10 countries participating in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. METHODS: Between 1995 and 2000, 36,034 participants aged between 35-74 years completed a standardized 24-h dietary recall using a software programme (EPIC-Soft) that recorded the place of food/drink consumption. Eating OH was defined as the consumption of foods and beverages anywhere other than in household premises, irrespective of the place of purchase/preparation. Nutrient intakes were estimated using a standardized nutrient database. Mean intakes were adjusted for age and weighted by season and day of recall. RESULTS: Among women, OH eating contributed more to total fat intake than to intakes of protein and carbohydrates. Among both genders, and particularly in southern Europe, OH eating contributed more to sugar and starch intakes and less to total fibre intake. The contribution of OH eating was also lower for calcium and vitamin C intakes. The composition of diet at home was different from that consumed out of home in southern countries, but was relatively similar in the north. CONCLUSIONS: In northern Europe, OH and in-home eating are homogeneous, whereas southern Europeans consider OH eating as a distinctive occasion. In most centres, women selected more fat-rich items when eating out.